Efeito da adição de gálio em catalisadores de platina suportados em carbono na eletro-oxidação de álcoois - Santos, Deise Menezes (2016)
Platinum catalysts supported on carbon are frequently used in the electro-oxidation of alcohols such as ethanol and glycerolintoproton exchangemembrane fuel cells. The slow kinetics of oxidation of alcohols, the catalyst poisoning and incomplete oxidation products are bordersof this technology. The addition of metalsintoplatinum has been widely investigated, though very scarce information about PtGaaction in methanol oxidationisreported. In this study, PtGa/C were synthesized by thermal decomposition of the polymeric precursor method to investigate the catalytic activity against the oxidation of ethanol and glycerol. The morphological and electrochemical characterizations were made by: Thermogravimetric analysis, X-ray diffraction, transmission electron microscopy, energy dispersive spectroscopy X-ray, Cyclic voltammetry, chronoamperometry, chronopotenciometry and activation energy test. Morphological characterization showed particles from 7.2 nm to 18.9 nm, solid solution of gallium and platinum, heterogeneous distribution of the particles on the carbon support, platinum on face-centered cubic structure and gallium oxide in the compositions. The unprecedentedstudy of PtGa/C catalytic activity forthe electro-oxidation ofethanol and glyceroldisclosed in the addition of gallium to platinum increases the catalytic activity and stability compared topure platinum, according toelectrochemical tests.